Methane emissions estimate from airborne measurements over a western United States natural gas field. Issue 16 (27th August 2013) - Karion, Anna; Sweeney, Colm; Pétron, Gabrielle; Frost, Gregory; Michael Hardesty, R.; Kofler, Jonathan; Miller, Ben R.; Newberger, Tim; Wolter, Sonja; Banta, Robert; Brewer, Alan; Dlugokencky, Ed; et al.
Abstract [1] Methane (CH4) emissions from natural gas production are not well quantified and have the potential to offset the climate benefits of natural gas over other fossil fuels. We use atmospheric measurements in a mass balance approach to estimate CH4 emissions of 55 ± 15 × 103 kg h−1 from a natural gas and oil production field in Uintah County, Utah, on 1 day: 3 February 2012. This emission rate corresponds to 6.2%–11.7% (1σ) of average hourly natural gas production in Uintah County in the month of February. This study demonstrates the mass balance technique as a valuable tool for estimating emissions from oil and gas production regions and illustrates the need for further atmospheric measurements to determine the representativeness of our single‐day estimate and to better assess inventories of CH4 emissions.